SAT0129 Exploration of comorbidity indices in an ethnic rheumatoid arthritis subset. (15th June 2017) - Dowell, S; Kerr, G; Swearingen, C; Quinones, M; Berrian, J; Hochberg, S; ,
Abstract : Background: Comorbidity is common in ethnic patients with rheumatoid arthritis (RA) and often impact choice of DMARD therapy and clinical outcomes. In addition to simple summation of comorbidities, composite indices have been proffered as better predictors of poor clinical outcomes in patients with rheumatoid arthritis 1 . However, their applicability in ethnic RA subsets is unknown. Objectives: To compare composite to mean comorbidity indices in ethnic subsets with rheumatoid arthritis. Methods: Patients enrolled in the Ethnic Minority RA Consortium (EMRAC), with at least 6 months of followup data were analyzed. At enrollment, sociodemographic data and RA disease status, rheumatic disease comorbidity index (RCDI) 1 and comorbidity count (COUNT) 1 were analyzed amongst ethnic subsets. Spearman correlation was estimated between RCDI and COUNT while Poisson regression was used to model the differences in the comorbidity indices between race groups. Results: 453 EMRAC subjects were analyzed; 342 (81.4%) were female, average age was 58.9 (± 15.1) years, average duration 13.3 (±11.1) years and average follow-up length 2.1 (±1.4) years. Individual comorbid frequencies as well as comorbid indices are summarized in Table 1 . Spearman correlation between overall RDCI and COUNT was 0.90 (95% CI [0.88, 0.91], P<0.001). Hispanics, however, had significantly lower comorbidity indices scores than other race groups (RDCI Hispanic vs White P=0.003, Hispanic vs Black P=0.004, Hispanic vs Other P=0.038; COUNT Hispanic vs White P=0.012, Hispanic vs Black P=0.004, Hispanic vs Other P=0.151). Conclusions: In an ethnic RA subset, the RCDI and COUNT correlated well across ethnic groups. The comorbidity indices were not associated with RA disease activity at enrollment as assessed by the RAPID3. Hispanics had lower RCDI and COUNT scores compared to other race groups but also presented at a younger age which could account for this difference. More studies are needed to determine the predictive value of these indices in determining poor outcomes and mortality in this ethnic subset. References: England, BR et al. Arthritis Care Res. 2015 Jun; 67(6): 885–872. Disclosure of Interest: S. Dowell Grant/research support from: Bristol Myers Squibb, Pfizer, Genentech, Speakers bureau: Horizon Pharma, G. Kerr Grant/research support from: Bristol Myers Squibb, Pfizer, Genentech, C. Swearingen Grant/research support from: Bristol Myers Squibb, Pfizer, Genentech, M. Quinones Grant/research support from: Bristol Myers Squibb, Pfizer, Genentech, J. Berrian Grant/research support from: Bristol Myers Squibb, Pfizer, Genentech, S. Hochberg Grant/research support from: Bristol Myers Squibb, Pfizer, Genentech